The Relation of Market Orientation, Learning Orientation, and Competitive Advantages of F&B SMEs Using E-Commerce on Instagram - Christophorus Daniel; Vigo Lyonabel; Fransisca Andreani (Master of Management, School of Business and Management, Petra Christian University, 2024)
With the rise of e-commerce, many small and medium enterprises (SMEs), particularly in the food and beverage sector, focus on market orientation to foster a learning organization and gain competitive advantages. These SMEs often use Instagram for consumer communication. This research explores how market and learning orientations influence competitive advantages for food and beverage SMEs on Instagram. This quantitative study uses non-probability judgmental sampling, with data collected from 100 respondents. The analysis was conducted using SmartPLS 3.0 software. The findings reveal that market orientation positively affects learning orientation, positively influencing competitive advantages. Additionally, market orientation directly impacts competitive advantages. By understanding market orientation, food and beverage businesses can assess their strengths and weaknesses, enhancing their products and services to compete more effectively and deliver greater customer value.